Допоміжні історичні дисципліни: підсумки та перспективи студій (закінчення) - Перкун, В. (Український історичний журнал, 2021)
Метою статті є актуалізація таких питань, як генеза допоміжних історичних дисциплін в європейській науці XVIII ст., формування понятійного апарату, спроба акцентування уваги на потребі синхронного розвитку цього напряму досліджень з європейськими традиціями у частині методології, понятійної номенклатури, інтердисциплінарності, стан допоміжних історичних дисциплін у системі викладання на історичних факультетах, траєкторії їх вивчення в українській історіографії. Методологія полягає в компаративістському підході щодо осмислення ролі та місця допоміжних історичних дисциплін із застосуванням результатів таких гуманітарних наук і напрямів, як культурна антропологія, історія ідей, соціологія та акцентування на інтердисциплінарному підході при вирішенні дослідницьких завдань. Наукова новизна. Здійснюється синтетичний огляд розвитку допоміжних історичних дисциплін в Україні з аналізом їх актуального стану та проекцією на європейський досвід. Висновки. Наведений матеріал актуалізує кроки й завдання, які слід реалізувати задля виведення допоміжних історичних дисциплін на якісно новий рівень. Насамперед ідеться про системні зміни в підготовці фахівців. Пріоритетом має бути вивчення класичних та європейських мов, палеографії, дипломатики, що дасть змогу розуміти письмовий документ, дешифровувати культурні коди різних історичних періодів. Наступним кроком має стати сприйняття різних методологічних пропозицій в осмисленні того, чим є історична наука, який ефект має нести наукове дослідження, вихід із замкненого кола позитивізму. Украй важливо стежити за актуальною закордонною фаховою літературою, підтримувати контакти із зарубіжними колеґами, розуміти тенденції розвитку сучасної науки. Усе це дозволить системно змінити українську історичну науку та її фундамент, яким є допоміжні історичні дисципліни. The purpose of the article is to update such issues as genesis of this scientific area in European science of the 18th century, the conceptual apparatus of auxiliary historical disciplines, an attempt to emphasize the need for simultaneous development of this area of research with European traditions in terms of methodology, conceptual nomenclature, interdisciplinary, condition of the auxiliary historical disciplines in the system of teaching at historical faculties and trajectory of their study in Ukrainian historiography. The research methodology is based on the comparative approach in understanding the role and place of auxiliary historical disciplines using the research results of such humanities and areas as cultural anthropology, history of ideas, sociology and emphasis on the interdisciplinary approach in the solution of the research problems. The scientific novelty lies in the synthetic review of the development of auxiliary historical disciplines in Ukraine with the analysis of their current state of research with a projection on the European experience in the study of this area. The conclusions that emerge from the presented material show the systematic steps and tasks that should be carried out to bring the auxiliary historical disciplines to a qualitatively new level. First of all, we mean systematic changes in the training of specialists at historical faculties in institutes and universities. The priority should be the study of classical and European languages, paleography, diplomacy that will allow understanding the written document, having the ability to decipher the cultural codes of different historical periods. The next step should be a bolder openness to various methodological proposals in understanding of what historical science is, what effect scientific research should have, a way out of the vicious circle of positivism. It is extremely important to follow the current foreign scientific literature, contact with foreign colleagues not only to understand the trends on modern science but also to take an active part in it. This is how it will be possible to systematically change Ukrainian historical science and its foundation which are auxiliary historical disciplines.